Cannabinoids in Audiogenic Seizures: From Neuronal Networks to Future Perspectives for Epilepsy Treatment - Lazarini-Lopes, Willian; Do Val-da Silva, Raquel A.; da Silva-Júnior, Rui M. P.; Cunha, Alexandra O. S.; Garcia-Cairasco, Norberto (Frontiers in Behavioral Neuroscience, 2021)
Treatment with Cannabidiol (CBD) and modulation of the endocannabinoid system (ES) are currently prominent strategies for seizure treatment in both humans and animal models. CBD presents a great diversity of mechanisms of action, most of them directly and indirectly associated with modulation of the ES. In this context, understanding how CBD and the ES can interfere with the expression of both behavioral and electrophysiological aspects of epilepsies is extremely important. Audiogenic seizures (AS) are typically induced in genetically-developed susceptible rodent strains by means of exposure to high intensity acoustic stimulation (120 dB) and are usually expressed as generalized tonic-clonic seizures in the acute protocol and limbic seizures in chronic (kindling) protocols. In this scenario, it is initially important to understand the neuronal pathways associated with AS susceptibility and their expression. Brainstem structures are crucial for acute AS manifestation and are strongly associated with wild running and tonic-clonic seizures. Nevertheless, in a chronic protocol of AS, called audiogenic kindling (AK), behavioral, electroencephalographic (EEG) and histological alterations are observed. Initially, behavioral limbic seizures are displayed, similar to those described in electrically-induced amygdala kindling, with synchronous EEG forebrain activity, a clear signature of network extension, called recruitment. Behavioral and EEG alterations are followed by clear-cut expressions of cellular and molecular biomarkers of the consequent neuroplasticity. In the present review, we aimed to analyze the effects of CBD and ES modulation in several experimental models and strains of AS. We thus first begin with a revision of the brainstem and forebrain neuronal networks associated with acute and chronic AS. Although there is still a lack of literature, so far, studies with CBD have shown consistent anticonvulsant effects against AS, the modulation of ES however, presented a dual role on AS expression. In fact, while the activation of cannabinoid receptors induced anticonvulsant effects, antagonism of specifically CB1 receptors seems to be pro-convulsant in AS models. Therefore, current data reinforces the importance of targeting ES as a therapeutic alternative for epilepsies treatment.